1999
DOI: 10.1038/sj.jim.2900669
|View full text |Cite
|
Sign up to set email alerts
|

Biotin production under limiting growth conditions by Agrobacterium/Rhizobium HK4 transformed with a modified Escherichia coli bio operon

Abstract: The E. coli biotin (bio) operon was modified to improve biotin production by host cells: (a) the divergently transcribed wild-type bio operon was re-organized into one transcriptional unit; (b) the wild-type bio promoter was replaced with a strong artificial (tac) promoter; (c) a potential stem loop structure between bioD and bioA was removed; and (d) the wild-type bioB ribosomal binding site (RBS) was replaced with an artificial RBS that resulted in improved bioB expression. The effects of the modifications o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
9
0
4
Order By: Relevance
“…When the three strains were cultivated on the biotin-free MM agar pieces, only the biotin prototroph BFI-4 gave a very small, but undoubted, halo underneath and around the edge of the piece. Based on the halo size, the biotin concentration in the piece was calculated to be approximately 0.3 g of biotin per liter, which was several times to 10 times higher than the amount synthesized by wild-type E. coli (3,34). This reconfirmed that strain BFI-4 did synthesize biotin from glucose, albeit in a minute amount.…”
Section: Fig 4 Growth Responses Of Wild-type Strain Atcc 13032 and Itmentioning
confidence: 60%
See 1 more Smart Citation
“…When the three strains were cultivated on the biotin-free MM agar pieces, only the biotin prototroph BFI-4 gave a very small, but undoubted, halo underneath and around the edge of the piece. Based on the halo size, the biotin concentration in the piece was calculated to be approximately 0.3 g of biotin per liter, which was several times to 10 times higher than the amount synthesized by wild-type E. coli (3,34). This reconfirmed that strain BFI-4 did synthesize biotin from glucose, albeit in a minute amount.…”
Section: Fig 4 Growth Responses Of Wild-type Strain Atcc 13032 and Itmentioning
confidence: 60%
“…In addition to its biological significance, biotin is important commercially because of its various applications in the pharmaceutical, cosmetic, food, and livestock industries. The global market for biotin is estimated to be 10 to 30 tons and several hundred million U.S. dollars per year (3,4). Due to the lack of an efficient method of producing biotin through fermentation, its production has depended on a multistep chemical process originally developed by .…”
mentioning
confidence: 99%
“…Indeed one group has reported that the overexpression of bioH in the presence of other biotin biosynthesis genes significantly decreased biotin productivity (Koga et al, 1996). Other groups have also studied biotin overproduction in E. coli, but did not address engineering the pimeloylCoA pool (Shaw et al, 1999). Their approach involved reorganizing biotin biosynthetic genes into a single operon, bioBFCDA, expressed from the P tac promoter, and further optimization of this operon, by removing a stem loop after bioD and changing the RBS for bioB, which catalyzes the final step in biotin production.…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin biotin, a cofactor used in various carboxylation reactions, is an industrially important compound, added to feed stocks and cosmetics, comprising a world market of 10-30 tons per year (Shaw et al, 1999;Streit and Entcheva, 2003). However, the majority of biotin is produced via a chemical process, which has a high environmental burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation